Practices and Strategies of a Food Photographer as The New Petite Bourgeoisie in Digital Era - rihi, samuel (fakultas Desain Koomunikasi visual, 2024)
The development of digital media helps in the learning process, starting from seeing various food photo references on digital media platforms. Digital media makes it easier to learn food photography by self-taught until finally being a food photographers who are then ready to fight in the arena of food photography. This research aims to explore the practices and strategies carried out by food photographers to continue to exist in the realm of food photography in the era of digital media. The research method used is virtual ethnography, helped to observed the space for food photographers on Instagram. This research borrows a set of Bourdieu's theories related to the existence of the petite bourgeoisie and its journey to become the new petite bourgeoisie The era of digital media helped the existence of petite bourgeoisie from self-taught learning as well as food photographers. Photographs in the digital age provide petite bourgeois character, from self-taught learning related to food photography by Pinterest, TikTok, Instagram and YouTube. Every food photographer accumulates their capital to continue to move up in these levels in the food photography arena, namely by following the workshop or certification, doing various collaborations with clients, and then posting on social media, becoming a symbolic sign of their capital ownership. Food photographer have a tendency to always look aesthetic in everyday life. Food photography as an industry in the era of digital media and have working logic for the existence of a large number of viewers and likes, don’t become unpaid workers.